Effects of nodule characteristics on sampling number and duration of thyroid fine-needle aspiration biopsy: size does not matter, but cystic degeneration ratio does - TÜRELİ, DERYA; BUĞDAYCI, ONUR (SAGE PUBLICATIONS LTD, 2017)
Background: Ultrasound-guided fine needle aspiration biopsy (FNAB) of thyroid nodules, though the most accurate method to rule out malignancy, still has an inherent risk of yielding non-diagnostic specimens despite immediate assessment of specimen adequacy by an on-site cytopathologist. Purpose: To evaluate the effects of nodule volume and extent of cystic degeneration on total biopsy time and number of aspirations required for obtaining an adequate specimen. Material and Methods: A total of 510 patients underwent FNAB by a single radiologist accompanied by a cytopathologist who immediately assessed each sample for specimen adequacy. All sampled nodules were single and had one maximum diameter > 10 mm. Nodule volumes and cystic degeneration ratios were calculated prior to the intervention. Aspirations were repeated until the cytological material was deemed adequate by the cytopathologist; the number of aspirations and total biopsy time were then recorded. Results: Nodule volumes did not have significant effect on neither number of aspirations necessary for achieving specimen adequacy (P > 0.05) nor total biopsy time (r = -0.148 with P = 0.001). Predominantly cystic nodules, compared to predominantly solid nodules, required more sampling per nodule (4.58 +/- 1.11 vs. 3.44 +/- 1.19 aspirations, P = 0.001) and longer total biopsy time (16.40 +/- 6.19 vs. 11.15 +/- 6.18 min, P = 0.001). Conclusion: Predominantly cystic nodules require allocation of more time for biopsy. To ensure specimen adequacy when immediate specimen evaluation by an on-site cytopathologist is not possible, four samples from predominantly solid nodules and five passes through predominantly cystic nodules are required.
Keywords: Thyroid nodule; fine needle aspiration biopsy; number of aspirations; cystic degeneration ratio; nodule size; specimen adequacy; SPECIMEN ADEQUACY; BETHESDA SYSTEM; MANAGEMENT; DIAGNOSIS; INCIDENTALOMAS; CYTOPATHOLOGY; CYTOLOGY; DISEASE; TIME